The Impact of Vineyard Mulch on Soil Quality and Biological Diversity - Xinyao Duan; Tingting Luo; Yinting Ding; Xing Han; Hua Li; Hua Wang (Agriculture)
In vineyard mulching research, using biodegradable liquid mulch represents a novel and environmentally conscious approach to mulching. In comparison, grapevine branch return has been identified as the most effective mulching method. The effects of in-row mulching with two materials, biodegradable liquid film (BLF) and grapevine branches (GBM), on soil properties and microbial communities in the vineyard were assessed using a one-way horizontal block test with tillage as a control. The results indicated that the application of mulching resulted in a reduction in soil bulk weight; an increase in soil moisture; an enhancement in soil organic matter; and a notable elevation in soil nutrients content compared to the control treatment. Both mulching techniques increased the abundance and diversity of soil microorganisms, strongly correlated with soil physicochemical properties. The correlation analysis demonstrated that total organic carbon (TOC); total nitrogen (TN); total potassium (TK); nitrate nitrogen (NN); and available phosphorus (AP) had the most significant impact on shaping the microbial community, exhibiting a positive correlation with microbial diversity. Additionally, soil nutrients were identified to exert a more pronounced influence on the composition of the bacterial community.